In vivo depletion of B cells using a combination of high-dose cytosine arabinoside/mitoxantrone and rituximab for autografting in patients with non-Hodgkin's lymphoma - Voso, Maria Teresa; Pantel, Gitta; Weis, Mirjam; Schmidt, Petra; Martin, Simona; Moos, Marion; Ho, Anthony Dick; Haas, Rainer; Hohaus, Stefan (British journal of haematology, 2000)
We performed a pilot study including rituximab (Mabthera; IDEC-C2B8, Hoffmann-La Roche) with a sequential high-dose therapy protocol in 15 patients with follicular and three patients with mantle cell lymphoma and studied the potential of the chemoimmunotherapy to induce depletion of malignant B cells in vivo. Our treatment protocol included induction with three cycles of CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) chemotherapy, followed by peripheral blood stem cell (PBSC) mobilization using high-dose cytosine arabinoside (2 g/m2 every 12 h, days 1 and 2) and mitoxantrone (10 mg/m2, days 2 and 3) (HAM), preceeded by rituximab (375 mg/m2). The proportion of CD19+ B cells in blood and bone marrow decreased from 1·2 ± 0·4% to 0·13 ± 0·1% (P = 0·01) and from 2·7 ± 0·8% to 0·8 ± 0·5% (P = 0·03) respectively. The number of t(14;18)-positive cells in blood and bone marrow progressively decreased with treatment, as assessed by the quantitative real-time PCR assay in four patients. Conversion to PCR-negativity was achieved in the peripheral blood (PB) of seven informative patients. Leucaphereses were performed during the granulocyte colony-stimulating factor (G-CSF)-supported leucocyte recovery phase. In 17 of 18 patients, a median of 15·1 × 106 CD34+ cells/kg body weight (BW) could be harvested by a single procedure for enrichment by an immunomagnetic method. Leucapheresis products contained 51·3 ± 28·8 × 104 CD19+ B cells/kg BW (mean) and were t(14;18) PCR negative in all seven informative patients. These data compare favourably with results obtained in patients treated with the same regimen without rituximab. The high-dose therapy (n = 12 patients), including total body irradiation (14·4 Gy) and cyclophosphamide (200 mg/kg BW), was also preceeded by rituximab. Recovery of neutrophils to > 0·5 × 109/l and of platelets to > 20 × 109/l required a median of 13·5 and 11·5 d (range 11-24 and 9-24 d) respectively. In conclusion, the addition of the CD20 antibody to chemotherapy ensured tumour depletion in vivo and allowed the collection of PBSCs devoid of tumour cells and with conserved engraftment capability.
Frontdoor: 24 December 2001
Gesehen am 21.12.2021